# (4x-1)(3x-1)=

## Simple and best practice solution for (4x-1)(3x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (4x-1)(3x-1)= equation:

Simplifying
(4x + -1)(3x + -1) = 0
Reorder the terms:
(-1 + 4x)(3x + -1) = 0
Reorder the terms:
(-1 + 4x)(-1 + 3x) = 0
Multiply (-1 + 4x) * (-1 + 3x)
(-1(-1 + 3x) + 4x * (-1 + 3x)) = 0
((-1 * -1 + 3x * -1) + 4x * (-1 + 3x)) = 0
((1 + -3x) + 4x * (-1 + 3x)) = 0
(1 + -3x + (-1 * 4x + 3x * 4x)) = 0
(1 + -3x + (-4x + 12x2)) = 0
Combine like terms: -3x + -4x = -7x
(1 + -7x + 12x2) = 0
Solving
1 + -7x + 12x2 = 0
Solving for variable 'x'.
Factor a trinomial.
(1 + -4x)(1 + -3x) = 0

#### Subproblem 1

Set the factor '(1 + -4x)' equal to zero and attempt to solve: Simplifying 1 + -4x = 0 Solving 1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = 0 + -1 -4x = 0 + -1 Combine like terms: 0 + -1 = -1 -4x = -1 Divide each side by '-4'. x = 0.25 Simplifying x = 0.25

#### Subproblem 2

Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333

#### Solution

x = {0.25, 0.3333333333}